My Visit to Abbas-Effendi in 1899 - Peeke,Margaret B. (1911)
Visit to Abdu'l-Bahá in 1899 by an American mystical author who subsequently became a Bahá'í.
Also in Pilgrim Accounts Collection.
Keywords: 1899; Akka, Israel; Cairo, Egypt; Margaret Peeke; Pilgrims notes